RESEARCH STATUS AND PROGRESS OF SHAFT PARTS DESIGN AND OPTIMIZATION (MT) - LI Gui; DING LiFen; LUO Ming; LIANG RenJie; ZHANG XiaoDi (Jixie qiangdu)
Improving the design process of shaft parts and improving the optimization index of shaft parts in the mechanical system can effectively improve the use performance of the entire equipment, while saving design time and ensuring design efficiency. By summarizing the research status and progress of shaft parts, a comprehensive analysis of the traditional design criteria, parametric design and optimization design of shaft parts has been carried out, and the main problems in the design process of shaft parts have been discovered. Suggestions on the design process of shaft parts based on analysis of working conditions, closed-loop design to achieve multi-objective optimization, establishment of an integrated design platform and system for shaft parts, and use of digital twins for advanced design are proposed, and the shaft is summarized and prospected. The future development trend of similar parts design. This provides an important research direction for realizing the comprehensive design of shaft parts, and also provides ideas for the intelligent development of shaft parts.